Resistance of Micro Small Medium Enterprises (MSMEs) Probolinggo City in the Era of the Covid-19 Pandemic - Tatik Amani; Hermanto Hermanto; Nadya Ika Putri (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
The research was conducted on MSME actors in Probolinggo City with the aim of knowing the factors that support their business resistance and helping provide input for solving what was experienced during the Covid-19 pandemic. This research uses quantitative associative analysis method with product quality, digital marketing as the independent variable and brand equity, income as the dependent variable. The sampling technique used a purposive sample with a total sample of 99 SMEs in Probolinggo City which came from the calculation of the slovin formula with of 10%. The results of the study indicate that there is a positive and partially significant effect for product quality and digital marketing variables on brand equity and income. Research also shows a relationship between brand equity and income variables. The correlation test shows that there is a relationship between brand equity and income, the higher the brand equity, the higher the income and vice versa. This result is an effort by researchers to provide input to MSME actors to survive and increase their income in the era of the COVID-19 pandemic by improving product quality and switching to digital sales.